System Quality, Service Quality, and Electronic Medical Record Adoption: User Satisfaction as Mediator in Regional Hospital Outpatient Care - Synthia Sari Toha; Rokiah Kusumapradja; Rian Adi Pamungkas (Alta Dharma Publisher, 2026)
Background: Electronic medical record (EMR) adoption is essential for improving documentation accuracy, information accessibility, service efficiency, and patient safety. In outpatient care, EMR adoption is particularly important because healthcare professionals work in a high-volume and time-sensitive service environment. Objective: This study aimed to examine the effects of system quality and service quality on EMR adoption, with user satisfaction as a mediating variable, among healthcare professionals in a regional hospital outpatient department. Method: A quantitative cross-sectional analytical study was conducted among 97 Care Provider Professionals in the outpatient department of Dr. Dradjat Prawiranegara Regional Hospital, Serang. Respondents were selected using purposive sampling. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Result: User satisfaction had a positive and significant effect on EMR adoption (? = 0.600; t = 4.075; p < 0.001). System quality significantly influenced user satisfaction (? = 0.202; t = 2.805; p = 0.005) and EMR adoption (? = 0.506; t = 5.573; p < 0.001). Service quality significantly influenced user satisfaction (? = 0.770; t = 12.540; p < 0.001), but its direct effect on EMR adoption was not significant (? = -0.164; t = 0.966; p = 0.334). The model explained 83.3% of the variance in user satisfaction and 78.4% of the variance in EMR adoption. Conclusion: EMR adoption in outpatient care is primarily influenced by system quality and user satisfaction. Service quality contributes to EMR adoption indirectly by improving user satisfaction rather than through a direct pathway. Recommendation: Hospitals should strengthen EMR system reliability, responsive technical support, user-centered training, and routine user satisfaction monitoring to sustain EMR adoption.